A method for improving the corrosion resistance of silane film on stainless steel sheets
By combining POSS modified montmorillonite with silane hydrolysate on stainless steel sheets, a modified silane film is formed, which solves the problem of insufficient corrosion resistance of silane films in the prior art, and has achieved a significant improvement in the density and corrosion resistance of the film layer, which meets the requirements of green and environmental protection.
Patent Information
- Application Number
- CN202310387620.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-04-12
AI Technical Summary
The prior art is difficult to effectively improve the corrosion resistance of silane film on stainless steel sheets, resulting in thin silane film thickness, low coating resistance, and difficult to film on the inner cavity surface during cathode electrophoresis, and there are defects of "collapse", which reduces corrosion resistance.
By mixing montmorillonite with aminated cage silsesquioxane and n-hexane, POSS modified montmorillonite is prepared and combined with silane hydrolysate to form POSS modified montmorillonite-silane hydrolysate, the stainless steel sheet is lifted and soaked and dried to form a modified silane film.
It significantly improves the thickness and corrosion resistance of the silane film, enhances the density and hydrophobicity of the film layer, improves the bonding force between the metal substrate and the coating, improves the corrosion resistance, and conforms to the concept of green and environmental protection.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anti-corrosion stainless steel processing, and in particular relates to a method for improving the corrosion resistance of a silane film of a stainless steel sheet. Background Art
[0002] Sun Zhendong et al. used a one-step method to mix and hydrolyze γ-glycidyloxypropyltriethoxysilane (γ-GPS) and BTSE in a ratio of 2:3 to prepare a double silane composite film on the surface of Q235 steel. The double silane composite film as an intermediate layer enhances the adhesion of the epoxy resin coating to the substrate surface and improves the corrosion resistance of the epoxy resin coating. Zhao Zhijie et al. found that when a double-layer silane film is prepared by a two-step method, the dip-coating order of the silane solution will affect the corrosion resistance of the film. Dipping γ-aminopropyltriethoxysilane first helps to form more Si-O-Mg bonds and forms a more stable Si-O-Si structure with the later dip-coated bis-1,2-[γ-triethoxysilylpropyl]-tetrasulfide silane. The compactness and hydrophobicity of the film layer are improved, thereby enhancing the corrosion resistance of the silane film. However, it is difficult to achieve high corrosion resistance by simply preparing a double-layer silane film, and the double-layer silane film still needs to be further modified to meet industrial needs. Song Jian et al. used 1,2-bis(triethoxysilyl)ethane (BTSE) and 1H,1H,2H,2H-perfluorodecyltrichlorosilane (FDTS) to self-assemble and modify the surface of 304 stainless steel to prepare BTSE, FDTS silane films and BTSE-FDTS composite silane films. Li Minya et al. prepared 1H,1H,2H,2H-perfluorodecyltriethoxysilane (PFDS) self-assembled films on the surface of 430 stainless steel, but the assembly time is long, the process load, and the "collapse" defects of the self-assembled films are inevitable during the film formation process. The presence of these defects easily causes some faster reaction centers, which in turn reduces the corrosion resistance of the film. The silane film thickness is very thin, and its coating resistance is significantly lower than that of the phosphating film. During cathode electrophoresis, it is difficult to form a film on the surface of the inner cavity. Therefore, those skilled in the art are in urgent need of developing a method for improving the corrosion resistance of silane films on stainless steel sheets to meet the existing application market and performance requirements. Summary of the invention
[0003] In view of this, the present invention provides a method for improving the corrosion resistance of a silane film on a stainless steel sheet.
[0004] A method for improving the corrosion resistance of a silane film on a stainless steel sheet comprises conventional sandpaper polishing of the stainless steel sheet, followed by ultrasonic oil removal with acetone, industrial alcohol cleaning, rinsing with deionized water and drying, and further comprising the following steps: a first step, mixing montmorillonite with deionized water at a mass ratio of 7-9:100, allowing the montmorillonite to fully swell for 100-120 hours, taking an upper suspension and adding water to prepare 100 parts of a montmorillonite liquid with a mass fraction of 4-5%, then weighing 3-4 parts of an amino cage-shaped silsesquioxane, adding it to 12-15 parts of normal hexane under stirring until it is completely dissolved, then adding 2-4 parts of a hydrochloric acid solution with a mass concentration of 5.5-7.5%, stirring evenly, and then adding the montmorillonite to the above suspension. The mixture was stirred at a speed of 500-800 rpm for 2-4 hours, and magnetically stirred at 50-60° C. for 4-6 hours, then filtered, washed with deionized water for three times, vacuum dried and ground to obtain POSS modified montmorillonite; the second step, preparation of silane hydrolyzate: the obtained POSS modified montmorillonite, silane, ethanol and deionized water were mixed evenly, the pH was adjusted to 5-7 with glacial acetic acid, mixed evenly, ultrasonicated for 1 hour and placed for 24 hours to fully hydrolyze the silane solution to obtain POSS modified montmorillonite-silane hydrolyzate, wherein the mass ratio of POSS modified montmorillonite, silane, ethanol: deionized water is 1.53-1.68: 2-3: 25-30: 7-10;
[0005] The third step is to soak the stainless steel sheet in the POSS modified montmorillonite-silane hydrolyzate for 6 to 8 minutes, then dry it in an oven at 70 to 80°C for 10 to 15 minutes, then take it out and soak it in distilled water, and air-dry it at room temperature for 3 to 5 minutes.
[0006] Furthermore, the silane is N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane or 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane.
[0007] Furthermore, the montmorillonite is sodium-based montmorillonite or calcium-based montmorillonite.
[0008] Furthermore, the stainless steel sheet is 316 stainless steel, 316L stainless steel or 304 stainless steel.
[0009] Furthermore, the ethanol is 95% industrial ethanol.
[0010] The method for improving the corrosion resistance of silane film of stainless steel sheet disclosed by the invention comprises the following steps: firstly, montmorillonite is used to prepare montmorillonite liquid, montmorillonite sheets can adsorb hydrated cations, thereby changing the interlayer spacing, and after being treated with hydrochloric acid, amination-type cage-shaped silsesquioxane enters the interlayer of montmorillonite sheets through ion exchange, and then plays a supporting role in the montmorillonite sheets by utilizing its rigid molecular structure, enters the interlayer of montmorillonite sheets to self-assemble in the form of bilayer arrangement, and the montmorillonite sheets modified by amination-type cage-shaped silsesquioxane have a larger interlayer spacing, and the thickness of the silane film is increased by adding POSS modified montmorillonite particles, so as to further improve the corrosion protection and mechanical properties, and at the same time, the Si-O-Si structure of POSS accounts for a relatively high proportion of the molecular structure, the Si-O-Si structure in the film layer is relatively large, the thickness of the silane film is significantly increased, and the double-layer silane film forms an effective physical barrier on the surface of the magnesium alloy, the path of the corrosive medium invading the stainless steel substrate becomes tortuous, and the time becomes longer, and the Si-O-Si structure is also easy to be combined with the silane film, so as to achieve a better anti-corrosion effect.
[0011] The method for improving the corrosion resistance of silane film of stainless steel sheet disclosed in the present invention can obtain an ultra-thin protective film layer with good coating and anti-corrosion effect on the upper surface of stainless steel sheet. Silane can form a strong covalent bond with the metal surface. As mentioned above, by forming a large number of dense Me-O-Si and Si-O-Si covalent bonds, the effect of silane and metal being firmly combined together is achieved. The bonding force between the metal substrate and the coating is enhanced, the corrosion resistance is improved, the bonding performance between the metal and the substrate is greatly enhanced, and its corrosion resistance is also greatly improved. The temperature is suitable, the film forming time is short, energy saving and emission reduction, phosphorus-free, and does not contain heavy metal ions such as nickel, manganese, and chromium. It conforms to the concept of green environmental protection and can be matched with post-processing procedures, such as electrophoresis, painting, etc., with low energy consumption and low cost. Implementation Example
[0012] Raw materials: Gaizhou Hengda Chemical N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, Jianping Longteng 600 mesh sodium montmorillonite, Guangde Guangxin 95% industrial ethanol;
[0013] The method for improving the corrosion resistance of silane film of 304 stainless steel sheet comprises the following steps: first, grinding the stainless steel sheet with sandpaper, grinding with 400 mesh and 1000 mesh sandpaper for 3 minutes respectively, then ultrasonically removing oil with acetone, cleaning with 95% industrial alcohol, rinsing with deionized water and drying; second, mixing montmorillonite with deionized water in a mass ratio of 8:100, making the montmorillonite fully swell for 110 hours, taking the upper suspension and adding water to prepare 100 parts of montmorillonite liquid with a mass fraction of 4.5%, then weighing 3.5 parts of Qiyue POSS-NH2 amino cage silsesquioxane, adding it to 13 parts of n-hexane under stirring until it is completely dissolved, then adding 3 parts of hydrochloric acid solution with a mass concentration of 7% and stirring evenly, then adding it into the above montmorillonite liquid, stirring at a speed of 600rpm for 3 hours, 55 ℃, magnetic stirring for 5h, then suction filtering, washing with deionized water for three times, vacuum drying and grinding to obtain POSS modified montmorillonite; the third step, preparation of silane hydrolyzate: the obtained POSS modified montmorillonite, silane, ethanol and deionized water are mixed evenly, pH 6 is adjusted with glacial acetic acid, mixed evenly and ultrasonicated for 1h and left for 24h to fully hydrolyze the silane solution to obtain POSS modified montmorillonite-silane hydrolyzate, wherein the mass ratio of POSS modified montmorillonite, silane, ethanol: deionized water is 1.68:2.5:28:8; the fourth step, the stainless steel sheet obtained in the first step is pulled and soaked in the POSS modified montmorillonite-silane hydrolyzate for 7min, then dried in an oven at 75℃ for 12min, then taken out and rinsed in distilled water, and air-dried at room temperature for 4min.
[0014] Product: The appearance of the film layer is consistent with the original color of the stainless steel material, there is no obvious change in the indoor anti-rust period of 30 days, the adhesion is level 1, the flexibility is 1mm, the impact resistance is greater than 50kg, and the corrosion resistance: there is no shedding, bubbles and rust after the salt spray test, and the film thickness is 687nm.
[0015] Comparative Example 1
[0016] Compared with Example 1, the POSS-modified montmorillonite in the fourth step is omitted in Comparative Example 1, and the remaining steps are the same.
[0017] Product: The appearance of the film layer is consistent with the original color of the stainless steel material, there is no obvious change in the indoor anti-rust period of 30 days, the adhesion is level 2, the flexibility is 1.5mm, the impact resistance is greater than 50kg, and the corrosion resistance: there is no shedding, bubbles and rust after the salt spray test, and the film thickness is 321nm. Example
[0018] NQ-562 Wanda silicone 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, Jianping Longteng 800 mesh sodium montmorillonite, a method for improving the corrosion resistance of 316L stainless steel sheet silane film, comprising the following steps: the first step, grinding the stainless steel sheet with sandpaper, grinding with 400 mesh and 1000 mesh sandpaper for 3 minutes respectively, then ultrasonically degreasing with acetone, cleaning with 95% industrial alcohol, rinsing with deionized water and drying; the second step, mixing montmorillonite with deionized water in a mass ratio of 7:100, allowing the montmorillonite to fully swell for 100 hours, taking the upper suspension and adding water to prepare 100 parts of montmorillonite liquid with a mass fraction of 4%, then weighing 3 parts of Qiyue POSS-NH2 amino cage silsesquioxane, adding 12 parts of n-hexane under stirring until completely dissolved, then adding 2 parts of 5.5% hydrochloric acid solution and stirring evenly, and then adding to the upper The montmorillonite solution is stirred at a speed of 500rpm for 2h, magnetically stirred at 50℃ for 4h, then filtered, washed with deionized water for three times, vacuum dried and ground to obtain POSS modified montmorillonite; the third step, preparation of silane hydrolyzate: the obtained POSS modified montmorillonite, silane, ethanol and deionized water are mixed evenly, pH 5 is adjusted with glacial acetic acid, mixed evenly and ultrasonicated for 1h and allowed to stand for 24h, so that the silane solution is fully hydrolyzed to obtain POSS modified montmorillonite-silane hydrolyzate, wherein the mass ratio of POSS modified montmorillonite, silane, ethanol: deionized water is 1.53:2:25:7; the fourth step, the stainless steel sheet obtained in the first step is pulled and soaked in the POSS modified montmorillonite-silane hydrolyzate for 6min, then dried in an oven at 70℃ for 10min, then taken out and rinsed in distilled water, and air-dried at room temperature for 3min.
[0019] Product: The appearance of the film layer is consistent with the original color of the stainless steel material, there is no obvious change in the indoor anti-rust period of 30 days, the adhesion is level 1 and the flexibility is 1mm, the impact resistance is greater than 50kg, corrosion resistance: there is no shedding, bubbles and rust after the salt spray test, and the film thickness is 653nm. Example
[0020] NQ-562 Wanda silicone 2-(3,4-epoxycyclohexyl)ethyl triethoxysilane, 600-mesh calcium-based montmorillonite from Shahai Bentonite Company, a method for improving the corrosion resistance of 316L stainless steel sheet silane film, comprising the following steps: the first step, grinding the stainless steel sheet with sandpaper, grinding with 400-mesh and 1000-mesh sandpaper for 3 minutes respectively, then ultrasonically degreasing with acetone, cleaning with 95% industrial alcohol, rinsing with deionized water and drying; the second step, mixing montmorillonite with deionized water in a mass ratio of 9:100, allowing the montmorillonite to fully swell for 100 hours, taking the upper suspension and adding water to prepare 100 parts of montmorillonite liquid with a mass fraction of 5%, then weighing 3 parts of Qiyue POSS-NH2 amino cage silsesquioxane, adding it to 15 parts of n-hexane under stirring until it is completely dissolved, then adding 4 parts of 7.5% hydrochloric acid solution and stirring evenly, and then adding into the above-mentioned montmorillonite solution, and stirred at a speed of 800rpm for 4h, magnetically stirred at 60℃ for 6h, then filtered, washed with deionized water for three times, vacuum dried and ground to obtain POSS modified montmorillonite; the third step, preparation of silane hydrolyzate: the obtained POSS modified montmorillonite, silane, ethanol and deionized water are mixed evenly, pH 5 is adjusted with glacial acetic acid, mixed evenly and ultrasonicated for 1h and allowed to stand for 24h, so that the silane solution is fully hydrolyzed to obtain POSS modified montmorillonite-silane hydrolyzate, wherein the mass ratio of POSS modified montmorillonite, silane, ethanol: deionized water is 1.68:3:30:10; the fourth step, the stainless steel sheet obtained in the first step is pulled and soaked in the POSS modified montmorillonite-silane hydrolyzate for 8min, then dried in an oven at 80℃ for 15min, then taken out and rinsed in distilled water, and air-dried at room temperature for 5min.
[0021] Product: The appearance of the film layer is consistent with the original color of the stainless steel material, there is no obvious change in the indoor anti-rust period of 30 days, the adhesion is level 1, the flexibility is 1mm, the impact resistance is greater than 50kg, and the corrosion resistance: there is no shedding, bubbles and rust after the salt spray test, and the film thickness is 676nm.
[0022] Note: Take the stainless steel sheets of Examples 1 to 3 for performance testing. Appearance of the film layer: Take 10 clean samples each and observe the appearance with a magnifying glass; Take 10 clean samples each and place them in a ventilated and cool room for 30 days, with a room temperature of 25°C and a humidity of 50%. The test samples cannot come into contact with other metals. After 30 days, observe whether the metal surface has rust and surface changes. Adhesion test: The samples are tested according to the cross-cut test method specified in GB / T 9286; the impact resistance and flexibility are tested according to the method specified in GB / T 1732. During the test, the temperature and humidity are constant at 25°C and 50%. The dried painted sample is placed flat on the anvil at the bottom of the instrument with the coating facing up, the weight is lifted, and then the weight is allowed to fall freely to impact the sample. The impacted part of the sample is not less than 15mm from the edge, and the edge distance of each impact point on each sample shall not be less than 15mm. Lift the weight, take out the sample, and observe with a 4x magnifying glass to determine whether the coating has cracks, wrinkles, peeling, etc. The impact force is 50kg. Neutral salt spray test: Use 5% sodium chloride salt solution, the pH value of the solution is adjusted to neutral 7.0 as the spray solution, and the test temperature is 35℃. Place the experimental metal sample in the salt spray test equipment, set the spray pressure to 0.11MPa, spray continuously for 500 hours, and set the sedimentation volume to 1.05ml / h. After the test, gently wash off the salt deposits on the surface of the test sample with running water, and then rinse in distilled water. The washing water temperature shall not exceed 35℃, and then restore for 2h under standard recovery atmospheric conditions, and then check the test sample according to the items specified in GB / T 1771 to observe whether the paint surface has peeling, bubbles and rust. The width of unilateral penetration corrosion under the film on both sides of the scribe line should not exceed 4mm. The thickness of the silane film is measured using an OU3500 digital coating thickness gauge.
Claims
1. A method for improving the corrosion resistance of a silane film on a stainless steel sheet, comprising conventionally grinding the stainless steel sheet with sandpaper, then ultrasonically degreasing the stainless steel sheet with acetone, cleaning with industrial alcohol, rinsing with deionized water and drying, characterized in that: The method further comprises the following steps: first, mixing montmorillonite with deionized water at a mass ratio of 7-9:100, so that the montmorillonite is fully swollen for 100-120 hours, taking the upper suspension and adding water to prepare 100 parts of montmorillonite liquid with a mass fraction of 4%-5%, then weighing 3-4 parts of amino cage-shaped silsesquioxane, adding it to 12-15 parts of normal hexane under stirring until it is completely dissolved, then adding 2-4 parts of hydrochloric acid solution with a mass concentration of 5.5%-7.5% and stirring evenly, then adding it to the above montmorillonite liquid, stirring at a speed of 500-800rpm for 2-4h, magnetically stirring at 50-60℃ for 4-6h, then filtering, washing with deionized water for three times, vacuum drying and grinding to obtain POSS modified montmorillonite; The second step is to prepare a silane hydrolyzate: the obtained POSS modified montmorillonite, silane, ethanol and deionized water are mixed evenly, the pH is adjusted to 5-7 with glacial acetic acid, and after mixing evenly, ultrasonicated for 1 hour and left for 24 hours to fully hydrolyze the silane solution to obtain a POSS modified montmorillonite-silane hydrolyzate, wherein the mass ratio of POSS modified montmorillonite, silane, ethanol: deionized water is 1.53-1.68: 2-3: 25-30: 7-10, and the silane is N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane or 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane; The third step is to pull and soak the stainless steel sheet in the POSS modified montmorillonite-silane hydrolyzate for 6-8 minutes, then dry it in an oven at 70-80°C for 10-15 minutes, then take it out and soak it in distilled water, and air-dry it at room temperature for 3-5 minutes.
2. The method for improving the corrosion resistance of the silane film of a stainless steel sheet according to claim 1, characterized in that: The first step montmorillonite is sodium-based montmorillonite or calcium-based montmorillonite.
3. The method for improving the corrosion resistance of silane film on stainless steel sheet according to claim 1, characterized in that: The third step stainless steel sheet is 316 stainless steel, 316L stainless steel or 304 stainless steel.
4. The method for improving the corrosion resistance of silane film on stainless steel sheet according to claim 1, characterized in that: The third step ethanol is 95% industrial ethanol.